2017
DOI: 10.1007/978-3-319-55134-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Design Decisions for a Real Time, Alcohol Craving Study Using Physio- and Psychological Measures

Abstract: The current study was a pilot for an alcohol craving monitoring study with a biosensor (E4 wristband) and ecological momentary assessment (EMA) smartphone app. The E4 wristband was evaluated on compliance rates, usability, comfort and stigmatization. Two EMA methodologies (signal-and interval-contingent design) were compared on data variability, compliance and perceived burden. Results show that both EMA methodologies captured variability of craving and compliance rates were between medium to low. The perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The embodiment experiences could be highly relevant for the study and use of wearable technology in health care. A substantial body of existing research addressed wearable technology in, among others, studies into health information recording [18,19], mood, sleep [20], personal sensing and biofeedback in mental health care [21-23], remote patient monitoring [24], medication adherence [25], and technology-assisted procedures [26]. Furthermore, there is an increasing use of wearable technologies that seamlessly fit into the user’s everyday lifestyle, can be worn on the body or mated with human skin, and continuously and closely monitor the user’s motion and vital signs (eg, pulse and blood pressure) [20,27], and as such provides the user with the information needed for self-assessment and change in health behaviors and health outcomes [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The embodiment experiences could be highly relevant for the study and use of wearable technology in health care. A substantial body of existing research addressed wearable technology in, among others, studies into health information recording [18,19], mood, sleep [20], personal sensing and biofeedback in mental health care [21-23], remote patient monitoring [24], medication adherence [25], and technology-assisted procedures [26]. Furthermore, there is an increasing use of wearable technologies that seamlessly fit into the user’s everyday lifestyle, can be worn on the body or mated with human skin, and continuously and closely monitor the user’s motion and vital signs (eg, pulse and blood pressure) [20,27], and as such provides the user with the information needed for self-assessment and change in health behaviors and health outcomes [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…1 ) for assessments (time-contingent design). The time contingent design was found to be least burdensome for this set of questions in a pilot study with students ( van Lier et al, 2017 ). At these set times the participants were asked to fill out some questions.…”
Section: Methodsmentioning
confidence: 99%
“…Participants had to turn the E4 wristband on when waking up and download the data and charge the wristband during the night. The pilot study also showed ( van Lier et al, 2017 ) that the usability of the wristband was high, but that participants wore the E4 from occasionally (few hours a day) to regularly (every day for five or more hours), therefore the micro incentives (further explained below) were added ( Musthag et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…While this shows promise, these studies were in the proof-of-principle phase therefore, more work is required to assess whether mobile technology can be used to provide reliable assessments of cognitive function. As for the assessment of personality profile and mood disturbances, there are groups that have monitored physiological signals such as heart rate variability and skin conductance to assess psychological function in different populations ( 116 118 ). The very limited evidence concerning the use of mobile and wearable technology for the assessment and management of non-motor symptoms highlights the opportunities in this field.…”
Section: Is It Possible To Improve Evidence-based Approaches To Managmentioning
confidence: 99%